Analysis of Mass Media Convergence (Case Study of the Shooting of Brigadier J by Former Propam Chief Ferdy Sambo) - Retno Barunawati Ayu; Ismi Dwi Astuti Nurhaeni; Prahastiwi Utari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Television as a conventional media is felt to still exist to withstand the onslaught of existing new media. However, currently, the majority of Indonesian people pay more attention to the following information regarding the murder of Brigadier J which involved the Head of the Propam Polri Division, Ferdy Sambo. This can be seen from the results of the Indonesian Political Indicator survey which showed that 76.2 percent of respondents had heard the news that the National Police Chief had announced Sambo as a suspect in the shooting of Brigadier J. Currently, many people have various framing and speculation regarding the mastermind behind the premeditated murder of Brigadier J. From the research conducted using a qualitative approach with the case study method with random sampling technique to 10 respondents who followed the Brigadier J murder case from television, it was found that some Indonesian people tend to assume that Ferdy Sambo was the main mastermind behind the Brigadier J shooting case, while Another assumption is that the public is of the view that Ferdy Sambo deliberately created a scenario to cover up the real incident